A Field Study on Matching with Network Externalities. - Baccara, Mariagiovanna; İmrohoroğlu, Ayşe; Wilson, Alistair J; Yariv, Leeat (American Economic Review, 2012)
We study the effects of network externalities within a protocol for matching faculty to offices in a new building. Using web and survey data on faculty's attributes and choices, we identify the different layers of the social network: institutional affiliation, coauthorships, and friendships. We quantify the effects of network externalities on choices and outcomes, disentangle the layers of the networks, and quantify their relative influence. Finally, we assess the protocol used from a welfare perspective. Our study suggests the importance and feasibility of accounting for network externalities in assignment problems and evaluates techniques that can be employed to this end. (JEL C78, C93, D62, D85, Z13)